Constructing Assessment for Evaluating Critical Thinking and Creative Problem-Solving Skills in the Lesson on Soundwave - Sri Zakiyah; Irma Rahma Suwarma; Dadi Rusdiana (Jurnal Penelitian Pendidikan IPA, 2024)
The objective of this article is to develop an instrument that can be used to assess the ability to solve creative problems (CPS) and critical thinking (CT) in the context of sound waves. This work is a component of our research on developing a teaching material that includes assessment as a component of the final product. The objective of this instrument is to evaluate students' critical thinking (CT) and critical problem-solving (CPS) abilities both before and after implementing the recently developed mobile learning teaching resources.  To construct the instrument, we adhere to the Facione and Osborn-Parness frameworks for CTs and CPSs. Validity testing and reliability testing comprise this instrument development process. We utilize Cronbach's Alpha to assess reliability and the content validity index to assess validity. According to the content validity index results, four of the six items in the CT instrument were determined to be valid. Conversely, the empirical validation test of the creative problem-solving skills instrument demonstrated that the results were valid and suitable for use. The Cronbach's Alpha results also indicated that both tools accurately evaluated students' creative problem-solving and critical reasoning abilities.